Submarine a guide tour inside a nuclear warship - Clancy, Tom (Berkley Books, 1993)
Clancy's first nonfiction blockbuster is now available in its first mass market edition. Taking readers on a tour of the "USS Miami," a Los Angeles-class nuclear submarine, this edition is updated to include new material on "Seawolf" and "Virginia."